Municipal Services and Financial Performance of Three Metropolitan Municipalities in South Africa - Zerihun, Mulatu F.; Mashigo, Mariann P. (Indian Journal of Finance, 2022)
The study aimed to evaluate the level of public satisfaction in the provision of municipal services. Specifically, the study examined the relationship between municipal services and financial performances in the three metropolitan municipalities in the Gauteng province of South Africa using secondary and primary data from a survey conducted in 2019. The study is based on the theory of social contract. The study employed both qualitative and quantitative techniques to examine the level of public satisfaction on municipal services delivered to the urban residents in the study areas. Data were gathered using semi-structured interviews and the annual financial statements from the three metropolitan municipalities in the Gauteng province of South Africa. The results from financial ratio indicators confirmed that the metropolitan municipalities were in a good financial position. However, the findings from financial ratio analysis should be used with utmost caution due to the major limitations and drawbacks associated with such financial measures. The content analysis in the study revealed that the demand for basic municipal services would remain high, costly, with severe backlogs, insufficient, and often with unresponsive management practices in the study areas. Moreover, the lack of entrepreneurial, innovative, and problem-solving skills and expertise among municipal managers compromised the provision of basic municipal services, and the residents remained unsatisfied in the three metropolitan municipalities of Gauteng Province. Other factors that contributed to the poor performances are also discussed.